Missing the "Moment of Grace" in James Baldwin's Going to Meet the Man. Issue 4 (2nd October 2018) - McCracken, David
Abstract: In "Going to Meet the Man, " James Baldwin illustrates Flannery O'Connor's theory that violence serves as a catalyst for a "moment of grace." Through the remembrances of the main character during one sleepless night, Baldwin depicts how Jesse has the potential to renounce the ideologies of White supremacy and toxic masculinity through his interaction with his wife Grace, whose name signifies her role as an agent of redemption. Through recollections about the violence that he inflicts as a sheriff as well as the violent lynching he observes as a child, Jesse moves closer toward contrition and ultimately salvation. In the end, however, Jesse maintains an allegiance with indoctrinated beliefs and rebukes the moment of grace, a rejection substantiated by his sexual assault of his wife.